HEGEMONI MASKULINITAS DALAM IKLAN MINUMAN BERENERGI (ANALISIS SEMIOTIKA TVC EXTRA JOSS DAN KUKU BIMA ENER-G) - I Nyoman Winata (Program Studi Ilmu Komunikasi FBIK Unissula, 2012)
Competition from products energy drinks encourages higher ad creativity. One is the energy drink product advertisements in the form of sachets. As sales of products that rely on the formation of the image of manliness or courage of men, energy drinks advertisements using various tagging system that puts the dominant masculinity. Through readings using semiotic analysis, look how masculine markers appear in two television commercials advertising the observed Extra Joss and Kuku Bima Ener-G with different ways. Even in television commercials Extra Joss, masculinity is placed on the highest dominance and eliminate altogether femininity. While the ad Kuku Bima Ener-G, tagging practices instead put femininity as subordinate of the masculine through hegemony. Marking a built in advertising myths naturalized hegemonic masculinity that does not appear as the cultural, but rather as a natural thing. As a result of the hegemonic masculinity get a strengthening and preservation through ideology. Opening the consciousness that the ad tagging system built from the myth would put that such ideologies as a result patriaki culture that does not have the essence so it can be destroyed.